Critical period of weed competiton on irrigated annual cotton - de Azevêdo, Demóstenes Marcos Pedrosa; Beltrão, Napoleão Esberard de Macêdo; da Nóbrega, Laudemiro Baldoíno; dos Santos, José Wellington; Vieira, Dirceu Justiniano (Pesquisa Agropecuaria Brasileira, 1994)
A field trial was conducted in Boa Ventura, PB, Brazil, in 1986, to investigate the effect of row spacing on critical period of weed competition on irrigated annual cotton (Gossypium hirsutum L.r. latifolium Hutch.). The results showed that, 1) the presence of weeds for a period of 20 days after plant emerging did not consistently affect cotton yield; 2) weed-free periods of 40, 60 and 80 days promoted higher cotton yields than the whole-cicle weed-free control; 3) wider row spacing cotton had a long critical period of weed competition (30 days) and the competitive process began earlier (16 days after emergence); and 4) for narrow row spacing cotton, the critical period was shorter (12 days) and the weed interference took place later (28 days) when the plants were more resistent to weed competition.
Keywords: Gossypium hirsutum; weed competition; weeding